Analisis Komunikasi Multikultural dalam Penanaman Toleransi Anak Panti Asuhan Bunda Serayu Banyumas - Wilibrordus Megandika Wicaksono; S Beki Istiyanto (Universitas Serang Raya, 2022)
Tolerance is still the homework in Indonesia. For the period 2008-2018, Wahid Foundation mentioned there were 1.420 violations by non-state actors and 1.033 violations by state actors related to intolerance. From this, the purpose of this study is to analyze early parenting in the context of multiculturalism at the Bunda Serayu Orphanage. The research uses the theory of symbolic interaction and the research method used is qualitative with narrative research. Data were collected through interview techniques, literature studies related to the stories of orphanage children, as well as observations at the orphanage. This orphanage takes care of children from various background. The result is caregivers instill a parenting pattern of equal affection for all. The differences that give rise to conflict are framed by egalitarian parenting patterns that characterize Banyumas culture. The encounter and interaction between children, caregivers, and peers at school and funder create to a new meaning of family. Visits to places of worship of other religions are also carried out as a means of getting to know the diversity. The multicultural communication creates to understanding, appreciation, and tolerance. This parenting pattern and visits to places of worship of other religions can be replicated to invest tolerance.